2016
DOI: 10.1063/1.4962012
|View full text |Cite
|
Sign up to set email alerts
|

Contributed Review: The novel gas puff targets for laser-matter interaction experiments

Abstract: Various types of targetry are used nowadays in laser matter interaction experiments. Such targets are characterized using different methods capable of acquiring information about the targets such as density, spatial distribution, and temporal behavior. In this mini-review paper, a particular type of target will be presented. The targets under consideration are gas puff targets of various and novel geometries. Those targets were investigated using extreme ultraviolet (EUV) and soft X-ray (SXR) imaging technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…More extensive gas cloud measurements have been made for high-Z noble gas targets which are used for high intensity laser-plasma interaction experiments. [119][120][121] Although these gas targets were spatially uniform far from the nozzle tips (as desired for those experiments), some evidence for small-scale vortex motion very near the nozzle tips was observed although the time dependence was not measured. 119 In rare instances, some vortex or arc-like structure was seen in the GPI light emission very near a single gas nozzle tip in the early Alcator C-Mod data.…”
Section: A Uniformity Of the Gas Cloudmentioning
confidence: 99%
See 1 more Smart Citation
“…More extensive gas cloud measurements have been made for high-Z noble gas targets which are used for high intensity laser-plasma interaction experiments. [119][120][121] Although these gas targets were spatially uniform far from the nozzle tips (as desired for those experiments), some evidence for small-scale vortex motion very near the nozzle tips was observed although the time dependence was not measured. 119 In rare instances, some vortex or arc-like structure was seen in the GPI light emission very near a single gas nozzle tip in the early Alcator C-Mod data.…”
Section: A Uniformity Of the Gas Cloudmentioning
confidence: 99%
“…IV A), the outward movement of blobs in the SOL, 48 and the absence of a dependence of GPI results on the gas puffing rate. 58 Nevertheless, it would be interesting to measure directly the gas cloud uniformity on the space and time scales of edge turbulence without plasma, as done for gas puff laser targets, 119 and also to calculate the expected gas cloud uniformity using a realistic fluid/molecular dynamics simulation code.…”
Section: A Uniformity Of the Gas Cloudmentioning
confidence: 99%
“…More details about the source employed are described in Refs. [19][20][21]. An AXUV-HS1 Si photodiode (mentioned in the paper as HS1) from IRD, USA, with an active area of 0.05 mm 2 and a capacitance of 20 pF, and a SiC detector, with an active area of 6.35 mm 2 and a junction capacitance of 100 pF, were placed at a distance of 108 and 170 mm, respectively, from the gas-puff source.…”
Section: Methodsmentioning
confidence: 99%
“…The double stream gas-puff target source represents a versatile alternative to perform experiments in small academic laboratories without the necessity to access to large-scale facilities, and can be regarded as complementary diagnostic tools for high spatial resolution imaging, obtaining additional information about the objects not directly available using other microscopy techniques. The laser-plasma source based on a double stream gas-puff target was successfully employed, thus far, for different applications [50], such as for shadowgraphy systems [51], radiography [52], radiobiology [53], photoionization [54], metrology [55], plasma channel studies [56] and, as will be shown extensively, imaging experiments [57][58][59].…”
Section: Introductionmentioning
confidence: 99%